Interaction of the non-phosphorylated peptide G7-18NATE with Grb7-SH2 domain requires phosphate for enhanced affinity and specificity - Gunzburg, Menachem J.; Ambaye, Nigus D.; Del Borgo, Mark P.; Pero, Stephanie C.; Krag, David N.; Wilce, Matthew C.J.; Wilce, Jacqueline A. (Journal of molecular recognition, 2012)
Src‐homology (SH2) domains are an attractive target for the inhibition of specific signalling pathways but pose the challenge of developing a truly specific inhibitor. The G7‐18NATE cyclic peptide is reported to specifically inhibit the growth factor receptor bound protein 7 (Grb7) adapter protein, implicated in the progression of several cancer types, via interactions with its SH2 domain. G7‐18NATE effectively inhibits the interaction of Grb7 with ErbB3 and focal adhesion kinase in cell lysates and, with the addition of a cell permeability sequence, inhibits the growth and migration of a number of breast cancer cell lines. It is thus a promising lead in the development of therapeutics targeted to Grb7. Here we investigate the degree to which G7‐18NATE is specific for the Grb7‐SH2 domain compared with closely related SH2 domains including those of Grb10, Grb14, and Grb2 using surface plasmon resonance. We demonstrate that G7‐18NATE binds with micromolar binding affinity to Grb7‐SH2 domain (KD = 4–6 μm) compared with 50–200 times lower affinity for Grb10, Grb14, and Grb2 but that this specificity depends critically on the presence of phosphate in millimolar concentrations. Other differences in buffer composition, including use of Tris or 2‐(N‐Morpholino)ethanesulfonic acid or varying the pH, do not impact on the interaction. This suggests that under cellular conditions, G7‐18NATE binds with highest affinity to Grb7. In addition, our findings demonstrate that the basis of specificity of G7‐18NATE binding to the Grb7‐SH2 domain is via other than intrinsic structural features of the protein, representing an unexpected mode of molecular recognition. Copyright © 2011 John Wiley & Sons, Ltd.